The Formal Structure of Kind Representations. Issue 10 (4th October 2021) - Haward, Paul; Carey, Susan; Prasada, Sandeep
Abstract: Kind representations, concepts like table, triangle, dog, and planet, underlie generic language. Here, we investigate the formal structure of kind representations—the structure that distinguishes kind representations from other types of representations. The present studies confirm that participants distinguish generic‐supporting properties of individuals (e.g., this watch is made of steel) and accidental properties (e.g., this watch is on the nightstand). Furthermore, work dating back to Aristotle establishes that only some generic‐supporting properties bear a principled connection to the kind, that is, are true of an individual by virtue of its being a member of a specific kind (e.g., telling time for a watch). The present studies tested the hypothesis that principled connections are part of the formal structure of kind representations. Specifically, they tested whether they structure a newly learned kind representation. Experiment 1 found that introducing a property of a newly encountered novel kind in any one of four linguistic frames that provide evidence that a property has a principled connection to a kind (e.g., "It has fur because it is a blick") led participants to infer a different conceptual consequence of principled connections (i.e., "There is something wrong with this blick, which does not have fur") for which they had no direct evidence. Two introduction frames that provided no evidence for principled connections (e.g., "Almost all blicks have fur") did not generate the same consequence. Experiment 2 found that all of the targeted properties were generic licensing, irrespective of the introduction frame. That the distinction between properties that bear principled connections to their kinds, and merely generic‐supporting properties structures novel kind representations, provides strong evidence that this distinction is part of the formal structure of kind representations.